A Peek into the Life of Online Learning Discussion Forums: Implications for Web-based distance learning - Allan, Mary (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Supporting quality learning in online discussion forums is an intricate task, particularly for e-tutors aspiring to facilitate vigorous interactive learning environments. I argue that the key to successful online discussion forums is the ability of e-tutors to provide learners with feedback well informed in the meaning making and knowledge advancement processes emanating from learner interactions. In this paper, a newly developed concept of providing e-tutors with the information they require is explored, exhibiting the Event Centre (EC) concept, through which tutors are able to obtain periodic “snapshots” of the occurrences throughout discussion forums, which highlight processes of meaning construction and knowledge advancement. The EC concept provides e-tutors with visual images that depict the links and routes through which participants using text messages convey meaning, construct knowledge, and create Socio-Informational networks within discussion forums.